Q : skills for success, reading & writing intro - McVeigh, Joe; Bixby, Jennifer (Oxford : Oxford University Press, 2011)
This Special Edition of Q: Skills for Success is a six-level series with a strong focus on academic skills and critical thinking. The 'Intro' level for Reading and Writing provides students with the essential foundations of English literacy. It uses inquiry-based units centered around big questions to engage students emotionally and intellectually, helping them develop the necessary vocabulary and writing techniques for academic success at an introductory level.
"Reading and writing intro"--Cover.
Keywords: English language -- Textbooks for foreign speakers; English language -- Composition and exercises; Reading (Higher education) -- Study and teaching